Optimizing thyroxine levels for enhanced buffalo sperm cryopreservation and fertility: a focus on quality, viability, and antioxidant protection - Salama, Maha S.; Ashour, Mohey A.; Shehabeldin, Ahmed M.; Omar, Mohamed E. A.; Soliman, Mohamed M.; Ghamry, Heba I.; Abdelmegeid, Mohamed; Shukry, Mustafa; Elolimy, Ahmed A. (Frontiers in Veterinary Science, 2025)
IntroductionThis study investigated the effects of adding thyroxine (T4) to buffalo semen on sperm quality, oxidative markers, apoptosis-like changes, and fertility.MethodsInitially, we tested a wide range of T4 concentrations (0.1, 0.3, 0.9, 2.7, and 8.1 µg/dL) to evaluate their impact on motility and viability.Result and discussionLower concentrations (0.1–0.9 µg/dL) improved total and progressive motility and viability compared to higher concentrations (2.7 and 8.1 µg/dL). We assessed optimized doses (0.25, 0.5, 0.75, and 1 µg/dL) based on these findings. The 0.75 µg/dL group showed superior sperm velocity, viability, motion parameters, membrane, acrosome, and DNA integrity in equilibrated and frozen-thawed samples. Antioxidant markers (GPx, SOD, TAC) were enhanced, while MDA and apoptotic/necrotic cell levels were reduced, particularly in the 0.75 µg/dL group. Fertility trials revealed higher cryosurvival and conception rates in thyroxine-treated groups. In conclusion, T4 supplementation, especially at 0.75 µg/dL, enhances cryopreservation outcomes and fertility potential of buffalo bull semen.